A Strategic Plan for Nuclear Disarmament: Engineering a Perfect Political Storm. Issue 1 (2nd January 2018) - Rydell, Randy
ABSTRACT: Rydell surveys two contrasting trends in nuclear disarmament: the lack of progress in eliminating nuclear arsenals and the growth of support for a treaty banning such weapons on humanitarian grounds. Both are guided by "political will." He describes the uses of this term in General Assembly and NPT deliberations. He stresses the importance of collective action on four levels: grassroots; coalitions of states; the nuclear-weapon states; and a common central forum at the United Nations. To sustain this political will, he argues for a "strategic plan" covering all these levels. Its core consists of activities involving actual reductions and destruction of warheads, bombs, and delivery systems, all undertaken with relevant controls for transparency, verification, irreversibility, universal membership, and legal bindingness. Sustaining it will require a blend of political forces yielding a "perfect storm" of pressures from all four dimensions of political will. The author stresses that prospects for disarmament rest on both ideals and self-interest. The article offers some thoughts on how to counter standard anti-disarmament criticisms and also identifies 10 practical initiatives to advance disarmament. The author relied on primary reference materials from the United Nations, the ban-treaty negotiations, NPT review conferences, and official statements by international officials.